In Vitro Activities of Ravuconazole and Four Other Antifungal Agents against Fluconazole-Resistant or -Susceptible Clinical Yeast Isolates - Cuenca-Estrella, Manuel (American Society for Microbiology, 2004)
The activities of ravuconazole and four other antifungal agents were tested against a collection of 1,796 clinical yeast isolates, including fluconazole-susceptible and -resistant strains. Ravuconazole was active against the majority of fluconazole-resistant isolates; but for 102 of 562 (18%) resistant isolates, mainly Candida tropicalis, Candida glabrata, and Cryptococcus neoformans, ravuconazole MICs were ≥1 μg/ml.